Penguatan Media Digital dan Pengembangan Strategi Intelektual Melalui Kegiatan Interaktif Bernuansa Budaya Lokal Di Yayasan Amara Bhawana Sastra - I Nyoman Bagus Pramartha; Komang Hari Santhi Dewi; Wayan Andrika Putera; I Kadek Sandy Dwiartha Putra; Mario Antonius Seda Mbei; I Gede Angga Bagus Aditya; Ni Made Tara Dwitya Putri; Ni Putu Anggi Amelia Ardan (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service program aims to strengthen digital media integration and enhance pedagogical competencies among teachers at the Amara Bhawana Sastra Foundation in Bangli, Bali. The program was initiated to address two critical gaps identified through preliminary observations: the absence of a professional institutional website for donor outreach and limited teacher proficiency in utilizing culture-based instructional media. The intervention involved a dual-faceted approach: the development of an official website and intensive training on the "DAKOGI" (Dakon Geometri)—an instructional tool based on traditional games. The training was conducted as an intensive eight-hour workshop with a 100% participation rate from the foundation’s teaching staff. Data were collected using pre-test and post-test instruments to measure competency shifts. Results indicated a significant improvement in teacher proficiency, with the average score rising from 43.3 (Poor Category) to 95.6 (Excellent Category). This improvement is further validated by a normalized gain score of 0.93, signifying high effectiveness. Post-training evaluations showed that 100% of participants mastered the integration of DAKOGI into lesson plans and active learning facilitation, while 95% successfully mastered game-based assessment techniques. This program demonstrates that integrating local cultural wisdom into modern pedagogical tools effectively revitalizes teacher capacity and broadens the institutional reach of social-educational foundations.